Minimally Invasive Video-Assisted Thyroidectomy: Almost a Decade of Experience at an Academic Center. Issue 10 (October 2016) - Frank, Ethan; Park, Joshua; Simental, Alfred; Vuong, Christopher; Liu, Yuan; Kwon, Daniel; Lin, Yi; Filho, Pedro Andrade
Minimally invasive video-assisted thyroidectomy (MIVAT) has gained acceptance as an alternative to conventional thyroidectomy. This technique results in less bleeding, postoperative pain, shorter recovery time, and better cosmetic results without increasing morbidity. We retrospectively assessed outcomes in 583 patients having MIVAT from May 2005 to September 2014. The study population was divided into groups according to periods: 2005 to 2009 and 2010 to 2014. Operative data, complications, and length of stay were collected and compared. Total thyroidectomy was undertaken in 185, completion thyroidectomy in 49, and hemithyroidectomy in 349. Malignancy was present in 127 (21.8%). Mean incision was 3.4 ± 0.7 cm and estimated blood loss was 23.7 ± 21.7 mL. Mean operative time was 86.5 ± 39.3 minutes for all operations, 78.5 ± 37.0 minutes for hemithyroidectomy, 70.9 ± 30.1 minutes for completion thyroidectomy, and 106.8 ± 41.3 minutes for total thyroidectomy. Postoperatively, 56 (9.6%) had unilateral vocal cord dysfunction, which resolved except for one case (0.17%). Fifty-nine patients (10.1%) developed hypocalcemia, but only three cases (0.51%) became permanent. Only one patient required readmission. In conclusion, MIVAT results in short operative times, minimal blood loss, and few complications and is safely performed in an academic institution.